AN ETHNOBOTANICAL SURVEY OF SPONTANEOUS PLANTS USED IN TRADITIONAL MEDICINE IN THE REGION OF AURES, ALGERIA - Karim Baziz (Université de M'sila, 2021)
Background: Like many regions in Algeria, the Aures abounds in an important ecological and floristic diversity. As a result, this region is the source of many plants used in traditional medicine. Despite this, the region is characterised by a lack of usable ethnobotanical data. Methods: In current study, semi-structured questionnaires with 701 inhabitants from September 2018 to March 2019 were conducted. Data recorded were analysed using frequency of citation (RFC) to identify the well-known and most useful species in the area. Results: This study allowed us to identify 112 medicinal spontaneous plants belonging to 47 families, of which Asteraceae, Lamiaceae, Amaranthaceae, Fabaceae, and Poaceae are the most represented and records new medicinal uses of 28 species. The leaves were the most used plant parts (28.86%), and the decoction (37.68%) represents the most frequently used mode of preparation. Also, the remedies were prepared essentially from single species (81.15%) and were used mainly in the treatment of digestive disorders (23.99%). The study has also shown that women, married people, the elderly, and illiterate people use traditional medicine much more than other categories. Conclusion: This study provides an ethnobotanical survey of medicinal plants with their frequency of citation as well as the part used, the diseases treated and the modes of application in the Aures region. It indicates that the local population has fairly extensive empirical and traditional knowledge of herbal medicine. However, this knowledge is threatened mainly because of the mode of transmission that is based on oral tradition, and urgent transcription is needed to avoid the loss of this heritage.
Keywords: ethnobotany; phytotherapy; spontaneous medicinal plants; traditional knowledge; vernacular plant name.